Vietnamese gender paradox: human rights education policy for sustainable development goal 4.7 - Xiem Nguyen Thi; Chu Thi Mai Huong; Tran Hanh Linh (Institute of Advanced Engineering and Science, 2026)
The research evaluates whether gender predicts teachers’ perceived gender inequality (PGI) and whether employee experience (EX) mediates this association in Vietnam’s feminized teaching workforce. An online cross-sectional survey involved 283 in-service teachers nationwide, administered between March and August 2025. Sample adequacy was confirmed before data collection using a root mean square error of approximation (RMSEA-based) structural equation modeling (SEM) power approach. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with 5,000-resample bootstrapping to test direct and indirect effects. Findings indicate that female teachers report higher PGI and less favorable EX than male teachers. EX strongly predicts perceived inequality and partially mediates the gender inequality relationship. The mediation pattern highlights practical evaluation targets in workload allocation, professional voice climate, and promotion feasibility. These results support substantive-equality reforms in school governance and institutionalized human rights education aligned with sustainable development goal (SDG) 4.7.